Silent Threats in the Blood Supply: Seroprevalence of Hepatitis B, Hepatitis C, HIV, Syphilis, and Malaria Among Blood Donors - Kumar, Vivek; kaur, Pandeep (Journal of Neonatal Surgery, 2025)
Background: Blood transfusion plays an essential role in modern healthcare, yet transfusion-transmissible infections (TTIs) remain a critical silent threat to blood safety. Hepatitis B virus (HBV), Hepatitis C virus (HCV), Human Immunodeficiency Virus (HIV), Syphilis, and Malaria continue to pose residual risks despite mandatory screening measures in India. Objective: To determine the seroprevalence of major TTIs among blood donors and evaluate their association with demographic characteristics. Methods: This observational study was conducted at the Department of IHBT, NIMS Hospital, Jaipur. A total of 941 apparently healthy blood donors were screened for HBV, HCV, HIV, Syphilis, and Malaria using standard ELISA and rapid serological methods. Demographic details were recorded, and statistical analysis was performed using the Chi-square test. Results: The overall TTI seroprevalence was 4.36%. HBV was the most prevalent infection (1.49%), followed by Syphilis (1.28%), HCV (0.85%), and HIV (0.74%). No malaria cases were detected. Age demonstrated a statistically significant association with HBV, HCV, and HIV positivity (p<0.05). The highest infection positivity occurred among donors aged 26–35 years. All 39 reactive donors were male, and the majority were replacement donors, indicating a higher-risk donor population. Conclusion: Although TTI prevalence in this region remains relatively low, silent carriers among first-time and replacement donors signify persistent transfusion risks. Strengthening voluntary donation, donor education, and advanced molecular screening (e.g., NAT) is essential to improve blood safety. Continuous surveillance of TTIs is crucial for preventive strategies in transfusion services.